Three new species of Helicopsyche von Siebold (Trichoptera: Helicopsychidae) from Brazil - Holzenthal, Ralph W.; Blahnik, Roger J.; Calor, Adolfo R. (Zootaxa, 2016)
Three new species of Helicopsyche subgenus Feropsyche (Trichoptera: Helicopsychidae) from southern and southeastern Brazil are diagnosed, described, and illustrated: Helicopsyche angeloi sp. nov. (Holotype male deposited in MZSP: Minas Gerais, Rio de Janeiro and São Paulo States), H. guara sp. nov. (Holotype male deposited in MZSP: Minas Gerais and Santa Catarina States) and H. lazzariae sp. nov. (Holotype male in MZSP: Paraná State). The first two species are similar to H. cipoensis Johanson & Malm, 2006, and H. timbira Silva, Santos & Nessimian, 2014, in having similarly shaped inferior appendages. However, the new species differs in the morphology and distribution of setae on the inferior appendages and tergum X. Helicopsyche lazzariae sp. nov. is unlike any other described species in the subgenus Feropsyche because of its broad deltoid-shaped inferior appendage and absence of a basomesal process on the inferior appendage. Characters important for diagnosing and describing new species of Helicopsyche (Feropsyche) are discussed. Finally, an updated checklist of the 23 species recorded for Brazil is presented.